Nucleotide regulation of vascular system - Alefishat, Eman (2011)
Previously, acyl derivatives of CoA were shown to antagonise human native and recombinant P2Y1 purine receptors. The main aim of this thesis was to study the effect of these endogenous nucleotide derivatives at endogenous P2Y1 receptors in blood vessels. Using isometric tension recordings, CoA, acetyl-CoA and palmitoyl-CoA (PaCoA) appeared to show selectivity for P2Y1 receptors (over P2Y2 and adenosine receptors) in the rat isolated thoracic aorta, with PaCoA being the most potent of the CoA derivatives used.